Correlates of injecting paraphernalia sharing among male drug injectors in Kermanshah, Iran: implications for HCV prevention. (3rd May 2020) - Mehrabi, Yadollah; Etemad, Koorosh; Noroozi, Alireza; Higgs, Peter; Nasirian, Maryam; Sharhani, Asaad; Khademi, Nahid; Hajebi, Ahmad; Noroozi, Mehdi; Shakiba, Ebrahim; Hamzeh, Behrooz; Azizmohammad Looha, Mehdi
ABSTRACT: Background: Sharing of injecting paraphernalia is known to contribute to hepatitis C virus (HCV) transmission amongst people who inject drugs. Objectives: In this paper, we identify the variables correlated with paraphernalia sharing among male drug injectors in Kermanshah city, western Iran. Methods: We enrolled 606 male drug injectors using snowball sampling in a cross-sectional study. Serological testing for HCV, HIV and HBV infections were performed after the completion of a bio-behavioral questionnaire. To identify variables associated with paraphernalia sharing, logistic regression analysis was completed. Results: The respondents were aged 18–65 years (mean±SD age of 36.7 ± 8.5). Approximately half of those surveyed (55.3% 335 individuals) reported sharing of injecting paraphernalia in the month prior to interview. Serological testing showed 54.8% (CI 50.8–58.7%), 6.4% (4.4–8.3%) and 2.9% (1.6–4.3%) positive result for HCV antibody, HIV antibody and HBs-Antigen, respectively. Being unemployed P < .001, single P < .001, having a history of drug overdose P < .001, having a previous positive HCV test P < .001, less than weekly attendance to needle/syringe programs P < .001and alcohol consumption P < .001 were all significant in the final model. Conclusions: With over half the participants reporting injecting paraphernalia sharing, providing more accessible harm reduction programs together with HCV testing and treatment programs may help to reduce the transmission of HCV among networks of drug injectors in Kermanshah city.